Polymer solid electrolyte film containing inorganic functional filler and preparation method thereof

By adding LATP@AlF3 and succinitrile to the polymer solid electrolyte film of all-solid lithium metal batteries, the problems of poor ion conductivity and interface instability of solid electrolytes are solved, and the performance and life of the battery are significantly improved.

CN119419348APending Publication Date: 2025-02-11JIANGHAN UNIVERSITY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411515072.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The application of solid electrolytes in all-solid-state lithium metal batteries generally has poor ionic conductivity, instability in interfaces and poor thermal stability, resulting in the growth of lithium dendrites and low Coulombic efficiency.

Method used

A polymer solid electrolyte film containing inorganic functional fillers is used to uniformly disperse LATP@AlF3 and succinitrile on the nanofiber separator to reduce the crystallinity of the polymer, provide a low-energy barrier lithium ion jumping site, and improve ion conductivity.

Benefits of technology

It significantly improves the ionic conductivity of polymer solid electrolytes, reduces the interface impedance between the solid electrolyte membrane and the electrode, inhibits the dendrite growth of lithium metal negative electrodes, and extends the battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419348A_ABST
    Figure CN119419348A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of lithium metal batteries, and particularly discloses a polymer solid electrolyte film containing an inorganic functional filler and a preparation method of the polymer solid electrolyte film. The thin film comprises a porous diaphragm, electrolyte slurry and inorganic filler, the electrolyte slurry and the inorganic filler are distributed on two sides of the porous diaphragm, the electrolyte slurry comprises a polymer capable of transmitting lithium ions, a lithium salt compound and an organic additive, and the surface of the inorganic filler is coated with metal fluoride with a certain thickness through an atomic layer deposition technology. And the thickness of the electrolyte layer on the two sides of the porous diaphragm is 20 microns. According to the polymer solid electrolyte (PPLS) film with the uniformly and compactly cured surface, the nanofiber diaphragm with excellent porosity and high mechanical strength is used as a skeleton support, the nanofiber diaphragm is coated with the solid electrolyte layer with relatively low crystallinity, so that the Li < + > ion conductivity of the polymer solid electrolyte (PPLS) is remarkably improved, and the polymer solid electrolyte (PPLS) film is simple in preparation process and low in cost. The large-scale continuous production is easy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium metal batteries and specifically discloses a polymer solid electrolyte film containing inorganic functional fillers and a preparation method thereof. Background Art

[0002] Lithium-ion batteries (LIBs) are a type of secondary battery system developed in the last century. In 1991, after six years of research and development, Sony launched its first LIBs product. The battery has a relatively simple structure and features high power density, high energy conversion efficiency, low-temperature start-up, no pollution, and light weight. The main components of LIBs are the positive electrode, negative electrode, separator, and electrolyte.

[0003] The lithium metal anode has the highest theoretical specific capacity (3860 mAh g -1 ) and the lowest potential (-3.040Vvs standard hydrogen electrode) is considered to be a promising negative electrode for the next generation of lithium batteries. When it is combined with a nickel-rich layered oxide (NCM) positive electrode, the assembled lithium metal battery (LMB) is considered to be a satisfactory choice for achieving high energy density in electrochemical energy storage systems. Among them, liquid electrolyte is an important component of LMB. Most of the commercial LIBs currently used in the market are in the form of liquid electrolytes. The function of the liquid electrolyte is to transfer Li shuttle between the positive and negative electrodes. + , and the development of LMB using traditional liquid electrolytes has been plagued by problems such as short cycle life, low efficiency and serious safety hazards caused by dendrite growth during lithium deposition. Solid electrolytes (SSE) have the advantages of low flammability, high thermal stability, no leakage and low explosion risk. Therefore, the development of all-solid-state lithium metal batteries (ASSLMBs) with high safety, good performance and superior energy density is an important way to eliminate safety hazards and break through the bottleneck of liquid electrolyte LMBs.

[0004] Among many solid electrolytes, polymer solid electrolytes (SPEs) are used in foldable ASSLMBs due to their outstanding flexibility, good processability and good interface adhesion. They are also considered to be key components of emerging flexible and wearable electronic devices. In ASSLMBs, the ionic conductivity of solid electrolytes is the most critical indicator for determining the performance of lithium metal batteries. It not only requires solid electrolytes to have excellent mechanical strength and flexibility, but also to achieve rapid conduction of electrons and ions. It also requires strong chemical stability to avoid side reactions with electrodes. In addition, the unique ion conduction mechanism of solid electrolytes is also the key to the realization of all-solid-state lithium metal batteries. Excellent ionic conductivity and stable interface contact make solid electrolytes closely related to the production cost and battery efficiency of all-solid-state lithium metal batteries. It can be said that the excellence of solid electrolyte performance directly affects the performance and service life of ASSLMBs. Summary of the invention

[0005] The present invention provides a polymer solid electrolyte (PPLS) film for solid-state lithium metal batteries and a preparation method thereof, so as to solve the problems of lithium dendrite growth and low coulombic efficiency caused by the poor ion conductivity, unstable interface and poor thermal stability of solid electrolytes currently used in all-solid-state lithium metal batteries, thereby solving the difficult problem of high energy density all-solid-state lithium metal batteries towards practical application.

[0006] In order to solve the above problems, the present invention adopts the following technical solutions:

[0007] A polymer solid electrolyte (PPLS) film containing inorganic functional fillers has a nanofiber membrane as a skeleton and LATP@AlF3 as a functional inorganic filler uniformly dispersed between polymer chain segments that transmit lithium ions, thereby reducing the crystallinity of the polymer and providing lithium ion hopping sites with lower energy barriers. Succinonitrile is intercalated between the polymer chain segments as a plasticizer to reduce the polymer crystallinity. The synergistic effect between the lithium-philic hopping sites provided by LATP@AlF3 and the ion transmission channels formed by succinonitrile jointly promotes the transmission of lithium ions and improves the ionic conductivity of the polymer solid electrolyte (PPLS).

[0008] A method for preparing a polymer solid electrolyte (PPLS) film containing an inorganic functional filler comprises the following steps:

[0009] (1) After the nanofiber membrane is cut neatly, it is placed in a 60°C oven for 2 hours to remove moisture.

[0010] (2) Lithium aluminum titanium phosphate (Li 1.3 Al 0.3 Ti 1.7 P3O 12 ) powder, and used ALD technology to coat and modify the metal fluoride AlF3 with different thicknesses to obtain LATP@AlF3 powder with a coating layer of 1.5-7nm thickness.

[0011] (3) PEO, PVDF-HFP, SN, and LITFSI were mixed in a ratio of 1:1:0.45:0.2, 40-50 ml of acetonitrile was added, and the mixture was stirred for 6 h using a magnetic stirrer. Subsequently, 5 wt% of LATP@AlF3 by weight of PEO and PVDF-HFP was added to the slurry, and the mixture was stirred slowly to obtain a uniform polymer electrolyte suspension.

[0012] (4) taking out the polymer electrolyte suspension obtained in step (3), using a coating machine to evenly coat the surfaces on both sides of the nanofiber separator prepared in step (1), and repeatedly coating each side twice. After cooling, transfer it to a 60° C. vacuum oven and let it stand for 12 hours to remove the acetonitrile solvent, thereby obtaining the polymer solid electrolyte (PPLS) film;

[0013] Furthermore, the nanofiber membrane in step (1) has a thickness of 15 μm and a pore size range of 3 to 4 nm, and the PEO molecular weight in step (2) is 60w mw, and the PVDF-HFP molecular weight is 10w mw.

[0014] Furthermore, in step (4), the coating thickness of the polymer electrolyte suspension on both sides of the porous membrane is 20 μm, and the surface density of the solid electrolyte on the porous membrane is 10 mg·cm -2 The mass ratio of the polymer electrolyte suspension to the porous membrane is 5:1.

[0015] Furthermore, the purpose of repeated coating in step (4) is to allow the polymer electrolyte suspension to fully infiltrate all pores of the nanofiber diaphragm, avoid the formation of pores that reduce the mechanical strength, and stabilize the structure of the polymer solid electrolyte (PPLS) film.

[0016] Compared with the prior art, the beneficial effects of the present invention are:

[0017] 1. In the polymer solid electrolyte film, the inorganic functional filler LATP@AlF3 is uniformly dispersed between the polymer segments used to transmit lithium ions. LATP reduces the crystallinity of the polymer. Succinonitrile is intercalated between the polymer segments as a plasticizer, which also reduces the crystallinity of the polymer. LATP provides lithium ion jumping sites with low energy barriers, which improves the transmission rate of lithium ions and the ionic conductivity of the polymer solid electrolyte (PPLS). On the other hand, the inorganic functional filler LATP@AlF3 and succinonitrile have a strong synergistic effect. Aluminum fluoride has a strong lithium affinity and is distributed around the LATP nanoparticles, so that A1F3 can effectively interact with lithium ions. The nitrile group has a strong polarity characteristic, which helps lithium ions jump on LATP and enter or leave the surface of LATP nanoparticles more smoothly. Thereby greatly improving the ionic conductivity of the polymer solid electrolyte. When the proportion of succinonitrile in the polymer is controlled to be 0.45, the synergistic effect of the inorganic functional filler LATP@AlF3 and succinonitrile is optimal, making the film ionic conductivity reach 2×10 -3 S / cm, reducing the interface impedance between the solid electrolyte membrane and the electrode.

[0018] 2. In the polymer solid electrolyte film, LATP@AlF3 provides a favorable inorganic component for the formation of SEI of lithium metal anode, and as a stable structure, it does not participate in the electrochemical reaction of the anode, inhibits the dendrite growth of lithium metal anode, and makes the high energy density of polymer solid electrolyte (PPLS) practical.

[0019] 3. In the polymer solid electrolyte film, the thickness of the nanocellulose diaphragm is 15μm. The purpose is to reduce the thickness of the final polymer solid electrolyte (PPLS) and shorten the transmission distance of Li ions. It is a uniform porous cellulose membrane with better toughness and mechanical strength than other cellulose membranes. It is not easy to break. As a skeleton, it has a light weight and a larger specific surface area. It can accommodate more polymer solid electrolytes (PPLS), reduce the consumption of raw materials, and greatly reduce the manufacturing cost.

[0020] 4. In the coating process of the polymer solid electrolyte film preparation method, the displacement rate of the applicator is 1 cm / s, and the coating is repeated twice in both forward and reverse directions to allow the polymer electrolyte suspension to fully infiltrate all the pores of the nanofiber diaphragm to avoid the formation of pores that reduce the mechanical strength, thereby obtaining a stable polymer solid electrolyte (PPLS) film structure.

[0021] 5. In the polymer solid electrolyte film of the present invention, the coating thickness of the solid electrolyte is controlled to be 20 μm and the surface density of the solid electrolyte is controlled to be 10 mg·cm -2 , so that the electrolyte slurry can fully infiltrate the pores of the nanofiber separator and provide good ionic conductivity, and can ensure the mechanical strength of the film, and there will be no large thickness difference in the subsequent 60°C desolventizing process, avoiding the problem that the solid electrolyte film is too thick, which will affect its density and power density, and too thin, which will not have enough mechanical strength. In addition, PVDF-HFP also has good thermal stability, which makes the resulting polymer solid electrolyte (PPLS) adaptable to high-temperature applications. PVDF-HFP has good compatibility with electrodes, especially on the negative electrode side, which reduces the occurrence of electrochemical side reactions and can extend the life of all-solid-state lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a physical picture of the solid electrolyte in step (3) of Example 1 of the present invention, wherein the size of the solid electrolyte is 10×10 cm;

[0023] Figure 2 The scanning electron microscope images of the solid electrolyte of the present invention, wherein (a) is a 30,000-fold magnification of the nanocellulose membrane used in the present invention, (b) is a 10,000-fold magnification of the solid electrolyte of Example 2, and (c) is a 6,000-fold magnification of the cross section of the solid electrolyte of Example 2;

[0024] Figure 3 Electrochemical impedance spectroscopy (EIS) test of a stainless steel / stainless steel symmetric cell assembled with the solid electrolyte prepared in step (4) of Example 2 of the present invention;

[0025] Figure 4 Electrochemical impedance spectroscopy (EIS) test of a stainless steel / stainless steel symmetric cell assembled with the solid electrolyte prepared in Example 2 of the present invention, and a control group was prepared according to the preparation method of Example 1, using only PEO (polyethylene oxide) in step (3), and finally preparing a solid electrolyte membrane composited with PEO and nanocellulose diaphragm;

[0026] Figure 5 Electrochemical impedance spectroscopy (EIS) test of a stainless steel / stainless steel symmetric battery assembled with the solid electrolyte prepared in Example 2 of the present invention, and a control group of polymer solid electrolytes prepared by ALD coating of different materials on LATP in Comparative Example 3 (PPLS@LiF@NFM) and Comparative Example 4 (PPLS@Al203@NFM);

[0027] Figure 6 Electrochemical impedance spectroscopy (EIS) test of a stainless steel / stainless steel symmetric cell assembled with the solid electrolyte prepared in Example 2 of the present invention, the control groups were respectively the polymer solid electrolyte (PPLS@NFM) prepared in Example 4 with a LATP coating layer of 0 nm and the polymer solid electrolyte (PPL@AlF3@NFM) without adding succinonitrile but with a LATP coating layer in Comparative Example 6;

[0028] Figure 7 The maximum current deposition density test of a Li / Li symmetric battery assembled with the polymer solid electrolyte (PPLS@NFM) prepared in Example 2 of the present invention and the solid electrolyte (PPS@NFM) prepared in Comparative Example 8;

[0029] Figure 8 The NCM811|Li battery assembled with the solid electrolyte prepared by the present invention is subjected to a cycle test at 25°C and 0.5C. The two curves are respectively the polymer solid electrolyte (PPLS@NFM) prepared with a 0nm LATP coating layer in Comparative Example 11 and the polymer solid electrolyte (PPS@AlF3@NFM) without adding LATP in Comparative Example 8;

[0030] Fig. 9 The tensile strength test of the solid electrolyte (PPLS@NFM) prepared in Example 2 of the present invention and the polymer solid electrolyte (PPS@NFM) of Comparative Example 9 without adding LATP is shown. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0032] The nanofiber membrane used in the following examples is an ultra-thin membrane with a thickness of 15 μm, a porosity of 70%, and a pore size range of 4 to 5 nm; the molecular weights of PEO and PVDF-HFP used are 60 w m w and 10 w m w (Purchased from Aladdin and McRae respectively).

[0033] Example 1

[0034] A solid electrolyte film with functional inorganic filler is prepared by the following method:

[0035] (1) After the nanofiber membrane is cut neatly, it is placed in a 60°C oven for 2 hours to remove moisture.

[0036] (2) The vacancy defect-rich LATP (300 nm) powder was modified with metal fluoride AlF3 using ALD atomic layer deposition technology to obtain LATP@AlF3. In this step, the thickness of the AlF3 modified layer was 1.5 nm.

[0037] (3) Using acetonitrile as a solvent, PEO (polyethylene oxide), PVDF-HFP (polyvinylidene fluoride-hexafluoropropylene copolymer), SN (succinonitrile), and LITFSI (lithium bis(trifluoromethanesulfonyl)imide) are mixed in a mass ratio of 1:1:0.45:0.2, and stirred in a magnetic stirrer at 60°C for 6 hours to uniformly disperse the suspension to obtain a slurry. Subsequently, LATP@AlF3 accounting for 5% of the mass of the polymer (PEO and PVDF-HFP) is added to the slurry, and the mixture is stirred slowly to obtain a uniform suspension. In this step, the solvent acetonitrile can be replaced by DMF (N,N-dimethylformamide).

[0038] (4) The polymer electrolyte suspension obtained in the above step is taken out, and the displacement rate of the coater is controlled to be 1 cm / s. The coater evenly coats the suspension on the dried nanofiber membrane, and repeatedly coats the front and back sides twice to allow the electrolyte suspension to completely penetrate into the pores of the nanofiber membrane. After cooling, it is transferred to a 60°C vacuum oven and allowed to stand for 12-24 hours to completely remove the acetonitrile solvent, thereby obtaining a polymer solid electrolyte (PPLS) film with a uniform and dense surface. In this step, the thickness of the coated polymer solid electrolyte (PPLS) layer is controlled to be 20 μm.

[0039] Preparation of NCM811 positive electrode sheet: NCM811, carbon black, and polyvinylidene fluoride (PVDF) were ball-milled and mixed in a mass percentage of 8:1:1 for 1 hour to obtain a uniform slurry, which was then scraped onto aluminum foil and placed in a vacuum drying oven and vacuum dried at 80°C for 24 hours.

[0040] In the above steps, the nanofiber membrane plays a unique supporting role. The prepared solid electrolyte can be rolled on a roller press. The height of the applicator is controllable, so the thickness of the solid electrolyte can be easily controlled to reach 20μm.

[0041] In the above steps, the surface density of the solid electrolyte is controlled at 10 mg cm -2 The method for controlling the surface density in this embodiment is: given the area of ​​the nanofiber membrane, weigh the masses of PEO and PVDF-HFP, succinonitrile and LITFSI in step (3), and then divide the sum of their masses by the area to obtain the surface density. In the above steps, 10 mg of solid electrolyte is required for each square centimeter of nanofiber membrane. The purpose of accurate weighing is to make the surface density of the solid electrolyte on the filter cloth reach 10 mg cm -2 , the formed solid electrolyte film is coated with a coater on a coater.

[0042] In this embodiment, because the size of the solid electrolyte surface density is related to the thickness, lithium affinity strength, porosity, density, and tensile strength, among which (1) Thickness: the greater the surface density, the greater the thickness. (2) Ionic conductivity: The ionic conductivity of the solid electrolyte is closely related to the crystallinity of the polymer. The lower the crystallinity of the polymer, the more free segments are available for lithium ion conduction. (3) Porosity: It decreases with the increase of the proportion of succinonitrile content. Porosity affects the power density. (4) Density: It increases with the increase of PEO and PVDF-HFP content. (5) Tensile strength: It increases with the increase of the surface density of the solid electrolyte film. Although the nitrile group of succinonitrile can be intercalated between the segments of the polymer to reduce the crystallinity of the solid electrolyte and improve its ionic conductivity, at 10 mg·cm -2It is difficult to ensure the mechanical strength of the polymer solid electrolyte film by continuing to increase the content of succinonitrile on the basis of the above, and after the subsequent solvent removal process at 60°C, there will be a large thickness difference due to the difference in the content of PEO and PVDF-HFP. If the solid electrolyte film is too thick, it will affect its density and power density, and if it is too thin, the mechanical strength will not be enough.

[0043] In this embodiment, the ALD technology in step (2) is performed with reference to the embodiment of patent CN1 18431676A.

[0044] Example 2

[0045] This example refers to the preparation method of Example 1 to prepare a solid electrolyte film with functional inorganic fillers. The difference from Example 1 is that in step (2), the thickness of the AlF3 modified layer is 2.0 nm. The thickness of the coated polymer solid electrolyte (PPLS) is controlled to be 20 μm.

[0046] Example 3

[0047] This example refers to the preparation method of Example 1 to prepare a solid electrolyte film with functional inorganic fillers. The difference from Example 1 is that in step (2), the thickness of the AlF3 modified layer is 7.0 nm. The thickness of the coated polymer solid electrolyte (PPLS) is controlled to be 20 μm.

[0048] Example 4

[0049] This embodiment refers to the preparation method of Example 1 to prepare a solid electrolyte film with functional inorganic fillers. The difference from Example 1 is that in step (2), the thickness of the AlF3 modified layer is 0 nm; in step (4), the thickness of the coated polymer solid electrolyte (PPLS) is controlled to be 20 μm.

[0050] Example 5

[0051] This embodiment refers to the preparation method of Example 1 to prepare a solid electrolyte film with functional inorganic fillers. The difference from Example 1 is that in step (2), the thickness of the AlF3 modified layer is 0 nm; in step (4), the thickness of the coated polymer solid electrolyte (PPLS) is controlled to be 45 μm.

[0052] Example 6

[0053] This embodiment refers to the preparation method of Example 1 to prepare a solid electrolyte film with functional inorganic fillers. The difference from Example 1 is that in step (2), the thickness of the AlF3 modified layer is 0 nm; in step (4), the thickness of the coated polymer solid electrolyte (PPLS) is controlled to be 50 μm.

[0054] Comparative Example 1

[0055] This example refers to the preparation method of Example 1 to prepare a solid electrolyte film with functional inorganic fillers. The difference from Example 1 is that in step (2), the thickness of the AlF3 modification layer is 2 nm; in step (3), the acetonitrile solvent is replaced with DMF.

[0056] Comparative Example 2

[0057] This example refers to the preparation method of Example 1 to prepare a solid electrolyte film with functional inorganic fillers. The difference from Example 1 is that in step (2), the thickness of the modified layer of AlF3 is 2nm, and in step (3), PEO, PVDF-HFP, SN, and LITFSI are mixed in a mass ratio of 1:1:0.2:0.2. After SN is reduced, the thickness of the coated polymer solid electrolyte (PPLS) is controlled to be 24um.

[0058] Comparative Example 3

[0059] This example refers to the preparation method of Example 1 to prepare a solid electrolyte film with functional inorganic fillers. The difference from Example 1 is that in step (2), LATP is coated with metal fluoride LiF using ALD coating technology, and the thickness of the metal fluoride layer is 2.0 nm.

[0060] Comparative Example 4

[0061] This embodiment refers to the preparation method of Example 1 to prepare a solid electrolyte film with functional inorganic fillers. The difference from Example 1 is that in step (2), LATP is coated with metal oxide Al2O3 using ALD coating technology, and the thickness of the metal fluoride layer is 2.0 nm.

[0062] Comparative Example 5

[0063] This example refers to the preparation method of Example 1 to prepare a solid electrolyte film with functional inorganic fillers. The difference from Example 1 is that in step (2), the thickness of the modified layer of AlF3 is 2nm, and in step (3), PEO, PVDF-HFP, SN, and LITFSI are mixed in a mass ratio of 1:1:0.7:0.2. After SN is increased, the thickness of the coated polymer solid electrolyte (PPLS) is controlled to be 17μm.

[0064] Comparative Example 6

[0065] This example refers to the preparation method of Example 1 to prepare a solid electrolyte film with functional inorganic fillers. The difference from Example 1 is that in step (2), the thickness of the modified layer of AlF3 is 2.0 nm, and in step (3), no succinonitrile is added. PEO, PVDF-HFP, and LITFSI are mixed in a mass ratio of 1:1:0.2 to prepare a polymer electrolyte suspension. The obtained polymer solid electrolyte is denoted as PPL.

[0066] Comparative Example 7

[0067] This example refers to the preparation method of Example 1 to prepare a solid electrolyte film with functional inorganic fillers. The difference from Example 1 is that step (2) is removed, and LATP is no longer added in step (3). PEO, PVDF-HFP, SN, and LITFSI are only mixed in a mass ratio of 1:1:0.1:0.2 to prepare a polymer electrolyte suspension. The obtained polymer solid electrolyte is denoted as PPS.

[0068] Comparative Example 8

[0069] This example refers to the preparation method of Example 1 to prepare a solid electrolyte film with functional inorganic fillers. The difference from Example 1 is that step (2) is removed, and LATP is no longer added in step (3). PEO, PVDF-HFP, SN, and LITFSI are only mixed in a mass ratio of 1:1:0.2:0.2 to prepare a polymer electrolyte suspension. The obtained polymer solid electrolyte is denoted as PPS.

[0070] Comparative Example 9

[0071] This example refers to the preparation method of Example 1 to prepare a solid electrolyte film with functional inorganic fillers. The difference from Example 1 is that step (2) is removed, and LATP is no longer added in step (3). PEO, PVDF-HFP, SN, and LITFSI are only mixed in a mass ratio of 1:1:0.45:0.2 to prepare a polymer electrolyte suspension. The obtained polymer solid electrolyte is denoted as PPS.

[0072] Comparative Example 10

[0073] This example refers to the preparation method of Example 1 to prepare a solid electrolyte film with functional inorganic fillers. The difference from Example 1 is that step (2) is removed, and LATP is no longer added in step (3). PEO, PVDF-HFP, SN, and LITFSI are only mixed in a mass ratio of 1:1:0.6:0.2 to prepare a polymer electrolyte suspension. The obtained polymer solid electrolyte is denoted as PPS.

[0074] Comparative Example 11

[0075] In this example, a solid electrolyte film having a functional inorganic filler is prepared by referring to the preparation method of Example 1. On the basis of Comparative Example 8, uncoated LATP is added in step (3), and then PEO, PVDF-HFP, SN, and LITFSI are mixed in a mass ratio of 1:1:0.2:0.2 to prepare a polymer electrolyte suspension. The obtained polymer solid electrolyte is denoted as PPLS.

[0076] The electrolyte membrane obtained in the above embodiment was cut into small discs with a diameter of 19 mm, and a stainless steel sheet (SS) | solid electrolyte | stainless steel sheet battery was assembled. The ionic conductivity of the solid electrolyte membrane was tested using electrochemical impedance spectroscopy (EIS) technology on an electrochemical workstation (CHI660c)0, with a frequency setting range of 0.1 to 1 MHz and a perturbation amplitude of 5 mV. The above operations were all completed in a glove box protected by an argon atmosphere. After the battery was assembled, constant current charge / discharge tests and related electrochemical performance tests were performed on a LAND CT2001A. The test results of ionic conductivity are shown in Tables 1, 2 and 3.

[0077] The polymer solid electrolyte (PPLS) prepared in the above example was used to prepare a lithium metal battery and the electrochemical performance was tested.

[0078] Table 1 Test results of ionic conductivity of solid electrolytes with different AlF3 coating thicknesses

[0079]

[0080]

[0081] Table 2 Test results of ionic conductivity of solid electrolytes coated with different materials

[0082]

[0083] Table 3 Test results of ionic conductivity of solid electrolyte coating at different thicknesses

[0084]

[0085] It can be seen from Comparative Examples 7 to 10 in Table 1 and the prior art that when preparing a solid electrolyte film, only succinonitrile (SN) is added without adding the inorganic functional material LATP. After testing, it is found that when the ratio of PEO, PVDF-HFP, SN, and LITFSI is 1:1:0.2:0.2, the ionic conductivity and power density of the solid electrolyte membrane are optimal. Although succinonitrile can reduce the crystallinity of the polymer, so that the free segments for lithium ion conduction in the polymer increase, the porosity of the solid electrolyte membrane decreases with the increase of the proportion of succinonitrile content, and the porosity affects the power density. Therefore, the power density of the solid electrolyte film prepared in Comparative Examples 9 and 10 is reduced. Therefore, when the ratio of PEO, PVDF-HFP, SN, and LITFSI in the polymer is controlled to be 1:1:0.2:0.2, the ionic conductivity and power density of the membrane are the largest.

[0086] In order to improve the ionic conductivity of the solid electrolyte film, inorganic functional materials can be further added to the above-mentioned polymers PEO, PVDF-HFP, SN, and LITFSI. For example, in the polymer of Comparative Example 11, the ratio of PEO, PVDF-HFP, SN, and LITFSI is 1:1:0.2:0.2. After adding LATP to the polymer, the ionic conductivity of the polymer solid electrolyte is slightly improved.

[0087] As shown in Comparative Example 11 compared with Examples 4 to 6, after adding LATP to the polymer, increasing the proportion of SN in the polymer has no significant effect on the improvement of the ionic conductivity of the solid electrolyte film, but reduces the mechanical strength of the solid electrolyte film and also reduces the power density. If the thickness of the solid electrolyte film is increased, the mechanical strength can be improved, but the ionic conductivity of the solid electrolyte film is significantly reduced. After adding LATP to the polymer, the proportion of SN in the polymer remains as that of Comparative Example 11, which is better.

[0088] In order to further improve the ionic conductivity of the solid electrolyte film, the surface of the added inorganic functional material can be modified, such as in Comparative Examples 3 to 4 and Comparative Example 2. For example, the ionic conductivity can be improved by coating LiF, Al2O3, and AlF3 on the surface of the inorganic functional material through atomic layer deposition technology;

[0089] The coating thickness of the modification layer also has a great influence on the ionic conductivity of the solid electrolyte film, such as Figure 3 The electrochemical impedance spectroscopy (EIS) test of the stainless steel / stainless steel symmetric cell assembled by the solid electrolyte prepared in Example 2 is shown. As shown in Table 1, when AlF3 is coated on the surface of the inorganic filler by atomic layer deposition technology, when the coating thickness is controlled to be 2nm, the ionic conductivity of the solid electrolyte film is optimally 2×10 ―3 S cm -1Too much or too little coating is not conducive to the transmission of lithium ions. This is because as the thickness of the coating increases, the path that lithium ions need to pass through in the electrolyte will also increase accordingly, which will cause the ions to overcome more energy barriers during lithium conduction, thereby reducing the ion conduction efficiency; in addition, too thick a coating may also introduce more grain boundaries and defects, which will increase the resistance to ion conduction. If the thickness of the surface modifier of the inorganic functional material is not optimized, the ionic conductivity of the solid electrolyte film may be reduced.

[0090] Further, as in Comparative Examples 1 to 2 and Comparative Examples 5 to 6, when the proportion of PEO, PVDF-HFP, SN, and LITFSI in the polymer is changed and the proportion of the succinonitrile content is adjusted, too high or too low a succinonitrile content cannot increase the ionic conductivity of the solid electrolyte film by an order of magnitude. Increasing a certain amount of succinonitrile can improve the ionic conductivity of the polymer solid electrolyte film, but continuing to increase succinonitrile will result in a decrease in the ionic conductivity of the polymer solid electrolyte film. When there is a surface-modified inorganic functional material in the polymer, adjusting the mass percentage of the plasticizer succinonitrile in the polymer to 45% can increase the ionic conductivity of the solid electrolyte film by an order of magnitude. However, as in Comparative Examples 7 to 8, when there is no surface-modified inorganic functional material in the polymer, adjusting the mass percentage of the plasticizer succinonitrile in the polymer is not effective.

[0091] As shown in Comparative Example 9 and Example 4, compared with Comparative Example 6, whether LATP is added to the polymer has little effect on the ionic conductivity of the solid electrolyte film. Referring to Comparative Examples 6 to 9, regardless of whether LATP is added to the polymer, the proportion of succinonitrile in the polymer is more critical to the improvement of the ionic conductivity of the solid electrolyte film. The preferred ratio of PEO, PVDF-HFP, SN, and LITFSI is 1:1:0.2:0.2, but as in Example 2, after LATP is coated with AlF3, the ionic conductivity of the solid electrolyte film is significantly improved. It may be that succinonitrile can play a synergistic role with LATP coated with AlF3.

[0092] Although the embodiments disclosed in the present invention are as above, the contents described are only embodiments adopted to facilitate understanding of the present invention and are not intended to limit the present invention. Any technician in the field to which the present invention belongs can make any modifications and changes in the form and details of implementation without departing from the spirit and scope disclosed in the present invention, but the patent protection scope of the present invention shall still be subject to the scope defined in the attached claims.

Claims

1. A solid electrolyte film containing an inorganic functional filler, characterized in that: It includes a porous diaphragm and an electrolyte layer distributed on both sides of the porous diaphragm, the electrolyte layer includes an electrolyte slurry and a lithium ion conductor, the electrolyte slurry includes a polymer capable of transmitting lithium ions, succinonitrile and a lithium salt compound, the surface of the lithium ion conductor is coated with a metal fluoride with a thickness of 1.5-7nm by atomic layer deposition technology, the thickness of the porous diaphragm is 15μm, and the thickness of the electrolyte layer on both sides of the porous diaphragm is 20μm.

2. The solid electrolyte film containing inorganic functional fillers according to claim 1, characterized in that: The lithium ion conductor comprises Li 1+x Al x Ti 2-x (PO4)3(LATP), Li 1+x Al x Ge 2-x (PO4)3(LAGP),Li3Zr2Si2PO 12 (LZSP); the metal fluoride includes one or more of ZnF2, SnF2, MgF2, AlF3, and the lithium ion conductor is 5% of the mass of the polymer that can transport lithium ions in the electrolyte slurry.

3. The solid electrolyte film containing inorganic functional fillers according to claim 1, characterized in that: The lithium salt compound includes one or more of LiClO4, LiTFSI, LiFSI, and LiBOB.

4. The solid electrolyte film containing inorganic functional fillers according to claim 1, characterized in that: The polymer matrix capable of transmitting lithium ions is at least one of polyethylene oxide, polymethyl methacrylate, polypropylene carbonate, polyvinylidene fluoride, and polyvinylidene fluoride-hexafluoropropylene.

5. The solid electrolyte film containing inorganic functional fillers according to claim 4, characterized in that: The polymer capable of transmitting lithium ions is polyethylene oxide (PEO) and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), the molecular weight of polyethylene oxide is 60w mw, and the molecular weight of polyvinylidene fluoride-hexafluoropropylene is 10w mw.

6. The solid electrolyte film containing inorganic functional fillers according to claim 5, characterized in that: The mass ratio of the polyethylene oxide, polyvinylidene fluoride-hexafluoropropylene, succinonitrile and lithium salt compound is 1:1:0.45:0.

2.

7. A method for preparing a solid electrolyte film containing an inorganic functional filler, characterized in that: The following steps are involved: (1) Pre-treating the porous diaphragm, cutting the porous diaphragm to a certain size, removing moisture, and drying for later use; (2) preparing an inorganic filler coated with atomic layer deposition, and modifying the surface of the inorganic filler, i.e., lithium ion conductor powder, with metal fluoride using ALD technology to obtain a lithium ion conductor powder coated with metal fluoride; (3) preparing an electrolyte slurry, mixing a polymer capable of conducting lithium ions, succinonitrile and a lithium salt compound in an acetonitrile organic solvent in a certain weight ratio, stirring the mixture thoroughly, then adding the metal fluoride-coated lithium ion conductor powder of step (2) accounting for 5 wt% of the polymer to the slurry, and continuing to stir the mixture slowly to obtain a uniform polymer electrolyte suspension; (4) preparing a solid electrolyte film, uniformly coating the polymer electrolyte suspension obtained in step (3) on both sides of the porous diaphragm prepared in step (1), coating each side twice, and standing in an oven to dry after cooling to fully remove the solvent to obtain the polymer solid electrolyte (PPLS) film.

8. The method for preparing a solid electrolyte film containing inorganic functional fillers according to claim 7, characterized in that: The porous membrane in step (1) is a nanofiber membrane with a thickness of 15 um and a pore size of 3-4 nm.

9. The method for preparing a solid electrolyte film containing inorganic functional fillers according to claim 7, characterized in that: The inorganic filler in step (2) is LATP (Li 1.3 Al 0.3 Ti 1.7 P3O 12 ) powder, using metal fluoride AlF3 as the coating layer of LATP, and the thickness of the coating layer is 1.5-7nm.

10. The method for preparing a solid electrolyte film containing inorganic functional fillers according to claim 7, characterized in that: In step (4), the coating thickness of the polymer electrolyte suspension on both sides of the porous membrane is 20 μm, and the surface density of the solid electrolyte on the porous membrane is 10 mg·cm -2 The mass ratio of the polymer electrolyte suspension to the porous membrane is 5:1.